Increasing The Sales Productivity Of 'Tette Chips' During the Time of The Covid-19 Pandemic, Through Digital Marketing: Case study of Blumbungan Village, Larangan Pamekasan District - Akhmad Fawaid (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2022)
The Covid-19 pandemic that hit the world and Indonesia, had an impact on the decline in the income of the “ceripik tette” sellers in Blumbungan Village, Larangan District, Pamekasan. Conventional marketing that is carried out by